Odpowiedzi

2009-09-30T16:35:41+02:00
A.
x+y=5
x-2y= -1

x=5-y
x-2y=-1
5-y-2y=-1
3y=6
y=2

x=5-y
x=5-2
x=3

y=2
x=3

B.
y-x=4
3(x+y)=24

y=4+x
3x+3y=24

y=4+x
x+y=8

x+4+x=8
2x=4
x=2

y=4+x
y=4+2
y=6

x=2
y=6

C.
x-2y=4
x+3= 2y

x=4+2y
x=2y-3

2y-3=4+2y
-3=4
układ sprzeczny (nie ma rozwiązania)

D.
3x-1= y-2
4x-3= -2(y-2)

3x=y-1
4x-3=-2y+4

3x=y-1
4x=-2y+7

12x=4y-4
-12x=6y-7

6y-7=4y-4
2y=3
y=1,5

3x=y-1
3x=1,5-1
3x=0,5
x=0,1(6)
Najlepsza Odpowiedź!
2009-09-30T16:47:11+02:00
A. x+y=5
x-2y= -1
x=5-y
x-2y=-1
5-y-2y=-1
-3y=-1-5
-3y=-6/(-3)
y=2
x+y=5
x+2=5
x=5-2
x=3



B. y-x=4
3(x+y)=24

y-x=4
3x+3y=24
y=4+x
3x+3(4+x)=24
y=4+x
3x+12+3x=24
6x=24-12
6x=12/6
x=2
y=4+x
y=4+2
y=6



C. x-2y=4
x+3= 2y
x=2y-3
2y-3-2y=4
y=7
x+3=2*7
x=11





D. 3x-1= y-2
4x-3= -2(y-2)
3x-1=y-2
4x-3=-2y+4
y=3x-1+2
4x-3=-2(3x-1+2)+4
4x-3=-6x+2-4+4
4x+6x=5
10x=5/10
x=1/2
y=3*1/2-1+2
y=1,5-1+2
y=2,5